Methodological aspects of teaching the basics of intercultural communication - Musagulova Ryskul Ekinovna; Chernichenko Irina Arkadievna; Yakovleva Polina Petrovna; Yefremtseva Tatyana Nikolaevna; Alipichev Aleksei Yurievich (SHS Web of Conferences, 2021)
The article considers the training method for teaching professionally oriented and intercultural communication. The use of training sessions during the study of educational topics in the classroom activates the students’ work, helps to consolidate the theoretical knowledge obtained, and motivates students for independent, collective, team work. There is no universally recognized classification of training. The article considers the division of training into three types: educational, personal, and professional. All these three types of training are used by the authors as the final stage of work on a certain topic. The work using the training method is described by the example of teaching students in the discipline “Professionally oriented foreign language”, which consists of two modules: professional communication and intercultural communication. The article provides examples of training in the first and second modules. In the first module, training helps to consolidate the so-called “flexible skills”, which cover the following topics: leadership, the ability to manage, criticize, resolve conflicts, speak publicly, persuade, negotiate, hold small-talk conversations, be a business person, learn from animals, birds, have business qualities of a leader. In the second module, students get acquainted with training on intercultural communication; learn to deal with people of other cultures, with the peculiarities of cultures, and with mistakes that can be made at the intercultural level.